Stable STIM1 Knockdown in Self-Renewing Human Neural Precursors Promotes Premature Neural Differentiation - Gopurappilly, Renjitha; Deb, Bipan Kumar; Chakraborty, Pragnya; Hasan, Gaiti (Frontiers in Molecular Neuroscience, 2018)
Ca2 + signaling plays a significant role in the development of the vertebrate nervous system where it regulates neurite growth as well as synapse and neurotransmitter specification. Elucidating the role of Ca2 + signaling in mammalian neuronal development has been largely restricted to either small animal models or primary cultures. Here we derived human neural precursor cells (NPCs) from human embryonic stem cells to understand the functional significance of a less understood arm of calcium signaling, Store-operated Ca2+ entry or SOCE, in neuronal development. Human NPCs exhibited robust SOCE, which was significantly attenuated by expression of a stable shRNA-miR targeted towards the SOCE molecule, STIM1. Along with the plasma membrane channel Orai, STIM is an essential component of SOCE in many cell types, where it regulates gene expression. Therefore, we measured global gene expression in human NPCs with and without STIM1 knockdown. Interestingly, pathways down-regulated through STIM1 knockdown were related to cell proliferation and DNA replication processes, whereas post-synaptic signaling was identified as an up-regulated process. To understand the functional significance of these gene expression changes we measured the self-renewal capacity of NPCs with STIM1 knockdown. The STIM1 knockdown NPCs demonstrated significantly reduced neurosphere size and number as well as precocious spontaneous differentiation towards the neuronal lineage, as compared to control cells. These findings demonstrate that STIM1 mediated SOCE in human NPCs regulates gene expression changes, that in vivo are likely to physiologically modulate the self-renewal and differentiation of NPCs.